2011
DOI: 10.1673/031.011.14601
|View full text |Cite
|
Sign up to set email alerts
|

Chemical Evaluation of African Palm Weevil,Rhychophorus phoenicis, Larvae as a Food Source

Abstract: The chemical properties of the African palm weevil, Rhychophorus phoenicis (F.) (Coleoptera: Curculionidae), larvae were evaluated using standard methodology. The chloroform-methanol extract yielded 37.12% on a dry basis. The oil was liquid at room temperature with a flash point of 36.0 °C. Analysis of the physical constants indicated values of 192.25 Wijs and 427.70 mg KOH/g as iodine and saponification, respectively. Fatty acid analysis of the extracted oil showed the presence of unsaturated fatty acids at l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
41
1
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 53 publications
(48 citation statements)
references
References 5 publications
1
41
1
2
Order By: Relevance
“…Again, since the nutrient composition of edible insect is influenced by their feed; another reason for the difference in protein content could be that the protein levels of PWL used in the formulation in this study were generally lower than the ones used by Adeboye et al () and Idolo (). Furthermore, defatted palm weevil larva (dry basis) has been found to have a protein content of 66.3% (Elemo et al, ). This implies that the protein content of the biscuit developed in this study can be improved by defatting of the larvae used in the production of PWLF.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Again, since the nutrient composition of edible insect is influenced by their feed; another reason for the difference in protein content could be that the protein levels of PWL used in the formulation in this study were generally lower than the ones used by Adeboye et al () and Idolo (). Furthermore, defatted palm weevil larva (dry basis) has been found to have a protein content of 66.3% (Elemo et al, ). This implies that the protein content of the biscuit developed in this study can be improved by defatting of the larvae used in the production of PWLF.…”
Section: Resultsmentioning
confidence: 99%
“…They are usually roasted, stewed or boiled, and served during storytelling or for special dishes on special occasions. Because of their high protein content, consumption of the larvae is currently being promoted as an alternative source of protein for preventing severe acute malnutrition (SAM) and possibly anemia (Elemo, Elemo, Makinde, & Erukainure, ; Parker et al, ).…”
Section: Introductionmentioning
confidence: 99%
“…However, few studies have focussed on phytochemicals from insects. Much of the studies done so far were centred on the nutritional compositions of edible insects that included the African palm weevil, Rhychophorus phoenicis (Elemo, 2011), Edible Stinkbug, E. delegorguei (Teffo et al, 2007) and a wide range of other insects (Defoliart, 1995;Banjo, Lawal, & Songonuga, 2006). Our study makes an effort to profile phytochemicals/bio-active compounds from this edible insect species and this could be the foundation of more refined experimental protocols for profiling these compounds in all edible insect species.…”
Section: Discussionmentioning
confidence: 99%
“…A number of insect species are known to sequester compounds from host plants and store them as defence mechanisms. This ability of insects to sequester and produce allelochemicals and phytochemicals has raised a lot of interest in the research for new drugs and search for alternatives to synthetic pesticides (Elemo, 2011;Silberbush, Markman, Lewinsohn, Bar, & Cohen, 2010;Teffo, Aderogba, & Eloff, 2010;Zaku, Abdulrahaman, Onyeyili, Aguzue, & Thomas, 2009;Moraes et al, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Most of the species of palm weevil have already been studied. Among the various species, the following had been profiled: African palm weevil R. phoenicis in Cameroon (Fogang Mba et al 2017;Womeni et al 2009Womeni et al , 2012, Nigeria (Adeyeye 2017;Edijala et al 2009;Ekpo and Onigbinde 2005;Elemo et al 2011;Ogbuagu et al 2011;Okunowo et al 2017;Omotoso and Adedire 2007) and Ghana (Atuahene et al 2017;Laar et al 2017); R. palmarum in Côte d'Ivoire (Dué et al 2009;Gbogouri et al 2013) and Nigeria (Adeyeye 2017), and R. ferrugineus in Egypt (Abdel-Moniem et al 2017) and Malaysia (Ali et al 2006). However, based on the review of available scientific literature, no nutritional information can be found for the species R. bilineatus.…”
Section: Introductionmentioning
confidence: 99%